miRNA-like duplexes as RNAi triggers with improved specificity - Betancur, Juan G.; Yoda, Mayuko; Tomari, Yukihide (Frontiers in Genetics, 2012)
siRNA duplexes, the most common triggers of RNA interference, are first loaded into an Argonaute (Ago) protein and then undergo unwinding via passenger strand cleavage, which requires the slicer activity of the Ago protein. In mammals, only Ago2 out of the four Ago proteins possesses such slicer activity. In contrast, miRNA/miRNA* duplexes often contain central mismatches that prevent slicer-dependent unwinding. Instead, mismatches in specific regions (seed and 3´-mid regions) promote efficient slicer-independent unwinding by any of the four mammalian Ago proteins. Both slicer-dependent and slicer-independent unwinding mechanisms produce guide-containing RNA-induced silencing complex (RISC), which silences target mRNAs by cleavage, translational repression, and/or deadenylation that leads to mRNA decay. In this review, we summarize our current knowledge of the RISC assembly pathways, and describe a simple method to rationally design artificial miRNA/miRNA*-like duplexes and highlight its benefits to reduce the unwanted “off-target” effects without compromising the specific target silencing activity.